The Effect of Physiotherapy in the Treatment of Juvenile Idiopathic Arthritis (Reabilitacijos mokslai: slauga, kineziterapija, ergoterapija, 2016)
Background. Juvenile idiopathic arthritis (JIA) is the most common and most diffcult chronic rheumatic disease in children. Exercise helps to avoid joint deformities or corrects them, also reduces pain and disease activity, normalizes physical function, growth and development, improves the patient’s quality of life. So far, there is no consensus on what kind of exercise is appropriate for children with juvenile idiopathic arthritis. Goal of the research. To defne the most often applied physiotherapy techniques and their impact on the treatment of children and adolescents with juvenile idiopathic arthritis analysing and summarizing scientifc articles. Methods. Twelve articles have been analysed. Systemic literature overview involved the articles on clinical research which were selected in the light of the following criteria: children with juvenile’s idiopathic arthritis; classic clinical tests performed; application of different physical exercises and survey of their accessibility; Childhood Health Assessment questionnaire; language and year of publication (2000–2015). Results. Research participants in the selected articles were 525 research children and adolescents with juvenile idiopathic arthritis. Their mean age ± SD was 11.2 ± 2.9 years (range 4–21 years). There were 348 (66%) girls and 177 (34%) boys. Aquatic therapy and Pilates workout had the strongest effect on pain relief, general physical performance and life quality, whereas balance and proprioception exercises had the best effect on balance and mobility. The results showed that regular physical exercises did not increase pain, they reduced the number of swollen joints, they were safe and effcient, also, that high-intensity aerobic exercises did not provide additional benefts, so it may suggest that low-intensity exercise program is more suitable for children with JIA because it is a slow and mild. Conclusion. Analysis of 12 articles have shown that general physical exercises (33.5%) and aquatic therapy (33.5%) are used most often, whereas balance-proprioception exercises are less frequent (17%), Pilates workout (8%) and Qigong relaxation (8%) are used very rarely. The most effcient methods for the improvement of general physical performance, quality of life, and reducing pain include aquatic therapy, Pilates workout and Qigong therapy. Balance-proprioception exercises are proved to be most effective in the improvement of mobility and balance.Keywords: juvenile idiopathic arthritis, physical exercises, training, physiotherapy, physical condition, life quality.